Development of the multiple regression models for estimating the force in tethered swimming (ts) and the power in semi-tethered swimming (sts) - Saijoh, T.; Ohba, M.; Shionoya, A. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The purposes of this study were to develop the systems, which measured the force in TS and the power in STS with ease and low cost and to investigate the relationships between the performance of swimming and force in TS and power in STS. Furthermore, the multiple regression models to estimate the force in TS and the power in STS were developed using several physical elements. The relationship between the force in TS and the power in STS in male was Y=1.82X-16.35 ( R=0.902 ) and this relationship was highly significant statistically( p<0.001 ). The relationship between the force in TS and the power in STS in female was Y=1.82X+9.44 ( R=0.800 ) and this relationship was highly significant statistically( p<0.001). Furthermore, the examples of the multiple regression model of the power in STS for male was aquired as follows; Power in STS = 0.33*Height+0.37*Finger Span+0.10*Vertical Jump+0.03*VJP-91.066** (r=0.85)